Challenges of the collaborative innovation system in public higher education in the era of industry 4.0 using an integrated framework - Xiaohua Li; Weibing Chen; Melfi Alrasheedi (Journal of Innovation & Knowledge (JIK), 2023)
Collaborative innovation systems comprise certain functions created by integrating a number of interconnected items in a certain order. These systems essentially create a connection between different elements for the achievement of a certain goal. To properly develop or transform a system, the relationships among the elements of the system must be well understood. Numerous structural models have been designed to be applied to collaborative innovation systems in higher education. Thus, the current paper deals with this gap by comprehensively analyzing the challenges that may arise for collaborative innovation systems in public higher education (PHE) in the era of industry 4.0, specifically in the context of developing countries. This study developed an integrated framework to identify and evaluate the main challenges of the collaborative innovation system in public higher education. This framework is applied to determine the subjective and objective weights of the main challenges of the collaborative innovation system in PHE in the era of industry 4.0. In addition, the framework is used to assess the preferences of PHE organizations over different main challenges of the collaborative innovation system in the era of industry 4.0. Finally, an empirical case study is taken to evaluate the main challenges of the collaborative innovation system in PHE in the era of industry 4.0. The results of this study found that; the holistic acceptance of the innovation with a weight value of 0.0614 has come out to be the most important challenge of the collaborative innovation system in PHE; in addition, the lack of technical infrastructure with a weight value of 0.0594 is the second most important challenge of the collaborative innovation system in the PHE, and educational policy has third with significance value 0.0588.
Keywords: O03; O31; O36; L08; I23; C44; 650; Collaborative innovation system; industry 4.0; public higher education; innovation; decision making